A systematic review of co-responder models of police mental health ‘street’ triage - Puntis, S; Perfect, D; Kirubarajan, A; Bolton, S; Davies, F; Hayes, A; Harriss, E; Molodynski, A (BioMed Central, 2018)
Background Police mental health street triage is an increasingly common intervention when dealing with police incidents in which there is a suspected mental health component. We conducted a systematic review of street triage interventions with three aims. First, to identify papers reporting on models of co-response police mental health street triage. Second, to identify the characteristics of service users who come in to contact with these triage services. Third, to evaluate the effectiveness of co-response triage services. Methods We conducted a systematic review. We searched the following databases: Ovid MEDLINE, Embase, PsycINFO, EBSCO CINAHL, Scopus, Thompson Reuters Web of Science Core Collection, The Cochrane Library, ProQuest National Criminal Justice Reference Service Abstracts, ProQuest Dissertations & Theses, EThoS, and OpenGrey. We searched reference and citation lists. We also searched for other grey literature through Google, screening the first 100 PDFs of each of our search terms. We performed a narrative synthesis of our results. Results Our search identified 11,553 studies. After screening, 26 were eligible. Over two-thirds (69%) had been published within the last 3 years. We did not identify any randomised control trials. Results indicated that street triage might reduce the number of people taken to a place of safety under S136 of the Mental Health Act where that power exists, or reduce the use of police custody in other jurisdictions. Conclusions There remains a lack of evidence to evaluate the effectiveness of street triage and the characteristics, experience, and outcomes of service users. There is also wide variation in the implementation of the co-response model, with differences in hours of operation, staffing, and incident response.